The Introduction of Classic Batik Motif to the Community Through Game - Elisa Purnamasari; Erdhi Widyarto; Albertus Dwiyoga Widiantoro (Soegijapranata Catholic University, 2017)
Batik is a wealth of Indonesian nation that became a cultural heritage and has been registered in the Representative of the Masterpiece of the Oral and Intangible Heritage of Humanity by UNESCO in 2009 [1]. The appearance of a variety of batik would be a pleasure for batik lovers so often used as clothing, furniture, or other equipment in everyday life.But the lack of knowledge of meaning and philosophy in batik itself so that batik is often being used indiscriminately without knowing the intentions contained in the batik itself and being a mistake in its use [2], especially classic batik is a batik that is still thick with tradition and custom philosophy in it [3].This report contains about the introduction of classic batik motifs and philosophies that are packaged in interactive educational games. This game is made by entering the element of trivia quiz as an evaluation material and equipped with batik information that can be read repeatedly outside the gameplay so as to enrich and give better understanding of the information in the game.From the results of a survey of 50 respondents from the age range between 13 - 30 years old located in Central Java and outside Central Java, shows that this educational game about batik can make respondents become richer with knowledge about the meaning and philosophy of classical batik. In addition, respondents also want to preserve batik as a nation's wealth.